Shameful Secrets and Self-Presentation: Negotiating Privacy Practices Among Youth and Rural Women in China. (January 2020) - Wang, Yini; Balnaves, Mark; Sandner, Judith
China, like the United States, has no defined concept of privacy in its Constitution and Chinese citizens have to work out how to negotiate their presence online, just as others elsewhere do. Online privacy in China has not received strong legislative protection compared with the U.S. and European countries as privacy has never written as an individual right in China's Constitution, nor in the Civil Law. Chinese privacy perceptions and everyday privacy practices in social media have not been fully examined. This article presents an original, ethnographic study of how 26 Chinese youth, men and women, and 25 older rural women from Changsha, south-central China are negotiating what counts as privacy online in their everyday practices. It finds out that youth group in Changsha has a stronger understanding of the technical level of deployment of the social media technologies, enacting both positive and protective self-presentation instantiated by "human flesh search, " "public online privacy, " and "improved firewall." However, the notion of shameful secrets touches on the protection of the reputation of those concerned, and social relationships play an important role in privacy boundary negotiation, common to both groups. This demonstrates that sociocultural contexts need to be taken into consideration and should be more nuancedly examined when studying online privacy and working out privacy protection methods.